2015
DOI: 10.1128/jvi.03399-14
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Fc Effector Mechanisms in the APOBEC3/Rfv3-Dependent Neutralizing Antibody Response

Abstract: Antiretroviral neutralizing antibody (NAb) responses are often evaluated in the absence of Fc-dependent immune effectors. In murine Friend retrovirus infection, Apobec3/Rfv3 promotes a potent polyclonal NAb response. Here, we show that the Apobec3/Rfv3-dependent NAb response correlated with virus-specific IgG2 titers and that thein vivoneutralization potency of Apobec3/Rfv3-resistant antisera was dependent on activating Fcγ receptors but not complement. The data strengthen retroviral vaccine strategies aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…To test if mA3/Rfv3-mediated enhancement of NAb responses occurs in LDV-free FV infection, WT and mA3 KO mice were infected with 10 4 SFFU of FV/LDV or FV and plasma NAb levels were evaluated at 28 dpi. Consistent with our previously published data [10, 25], mA3 KO mice had significantly lower NAb titers (3.4-fold) compared to WT mice during FV/LDV co-infection (Fig. 3a).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…To test if mA3/Rfv3-mediated enhancement of NAb responses occurs in LDV-free FV infection, WT and mA3 KO mice were infected with 10 4 SFFU of FV/LDV or FV and plasma NAb levels were evaluated at 28 dpi. Consistent with our previously published data [10, 25], mA3 KO mice had significantly lower NAb titers (3.4-fold) compared to WT mice during FV/LDV co-infection (Fig. 3a).…”
Section: Resultssupporting
confidence: 93%
“…In contrast to FV/LDV infections showing that mA3 influences NAb responses in the B6 background (Fig. 3a) [10, 25], the NAb titers between IFNAR KO and IFNAR/mA3 KO mice were not significantly different from each other (Fig. 4a).
Fig.
…”
Section: Resultsmentioning
confidence: 77%
“…Since CD8 + and CD4 + T cell responses were similar in FV-infected and co-infected mice, we next analysed the humoral response against the FV helper virus F-MuLV. Protective humoral responses during FV infection are mainly mediated by antibodies of the IgG2 subclass [50] and a beneficial effect of neutralising antibodies in the control of FV was described before [2729, 51–53]. Thus, we measured F-MuLV-specific IgG in the serum of FV-infected and L .…”
Section: Resultsmentioning
confidence: 99%
“…Sequence comparisons of monoclonal antibodies from Rfv3resistant versus Rfv3-susceptible mice suggested that protective neutralizing antibodies are associated with the IgG2c subclass, specific V H gene families, increased binding affinity to virions and higher somatic mutations (Halemano et al 2014). In passive transfer studies, the neutralizing activity of the antibodies was shown to be dependent on activating Fcγ receptors, but not on complement (Halemano et al 2015).…”
Section: B Cell Responses and Antibodiesmentioning
confidence: 99%